2014
DOI: 10.3390/ijms15069546
|View full text |Cite
|
Sign up to set email alerts
|

Nipple Discharge of CA15-3, CA125, CEA and TSGF as a New Biomarker Panel for Breast Cancer

Abstract: Breast cancer is the second leading cause of cancer death in women. Serum biomarkers such as cancer antigen 15-3 (CA15-3), cancer antigen 125 (CA125), and carcinoembryonic antigen (CEA) can be used as diagnostic and prognostic factors and can also provide valuable information during follow-up. However, serum protein biomarkers show limited diagnostic sensitivity and specificity in stand-alone assays because their levels reflect tumor burden. To validate whether biomarkers in nipple discharge may serve as novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 27 publications
2
41
0
Order By: Relevance
“…The levels of the four biomarkers in nipple discharge were significantly higher than those in the serum (P<0.01). Furthermore, our previous research shown CA15-3, TSGF, CA125 and CEA also had a certain clinical signifcance in the early diagnosis of tumors [2,4]. In this study, the sensitivity of the four serum tumor markes in combination in diagnosis of breast cancer was only 69.77%, in contrast, the dynamic combined detection both in discharge and serum was 97.67%, and the negative predictive value was 99.03%.…”
Section: International Conference On Mechanical Science and Engineerimentioning
confidence: 49%
See 3 more Smart Citations
“…The levels of the four biomarkers in nipple discharge were significantly higher than those in the serum (P<0.01). Furthermore, our previous research shown CA15-3, TSGF, CA125 and CEA also had a certain clinical signifcance in the early diagnosis of tumors [2,4]. In this study, the sensitivity of the four serum tumor markes in combination in diagnosis of breast cancer was only 69.77%, in contrast, the dynamic combined detection both in discharge and serum was 97.67%, and the negative predictive value was 99.03%.…”
Section: International Conference On Mechanical Science and Engineerimentioning
confidence: 49%
“…Abnormal nipple discharge is most commonly caused by benign conditions like intraductal papillomas, duct ectasia, papillomatosis, mastitis, fibrocystic changes [6][7][8][9]. The incidence of breast cancer in patients presenting with abnormal nipple discharge is between 5% to 21% [2,3,10]. A majority of patients with breast cancer who manifest with isolated nipple discharge have an early stage disease associated with ductal carcinoma in situ.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found as the first breast cancer‐associated antigen in 1984 7. After decades of experimental research on it, investigators had found that CA15‐3 could be used as diagnostic and prognostic factor and could also provide valuable information during follow‐up 8, 9, 10, 11. Thus, measurement of CA15‐3 is significant for breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%